Author’s “Ego” in “The Ballad of the Reading Gaol” - Tonyan, Marika (Armenian Folia Anglistika, 2014)
Oscar Wilde’s poem “The Ballad of the Reading Gaol” contains various narrative perspectives which convey the author’s and the protagonist’s points of view. In this work the roles of the author and the narrator are not differentiated, they are integrated in the subject of consciousness who manifests his “ego” in different modes: as the participant of the events, as their observer, as the transmitter of the main and secondary characters’ experiences and feelings, etc. The actualization of the existing standpoints becomes possible by means of pragmatic analysis of the text, and at the same time is, naturally, closely connected with the reader’s knowledge of the author’s background. By revealing the narrator’s meanings, the contextual implications, and by finding out the spacial characteristics of the text, an attempt is made at discovering the author’s subjectivity to a hopefully full extent.
Keywords: subject of consciousness; narrator; point of view; first-person narration; third-person perspective